Plan de negocios para la creación de una empresa comercializadora de cepillos dentales a base de bambú en Quinindé, Esmeraldas, Ecuador - Muñoz Cabrera, Denisis Georgina (2023)
The objective of this research is to develop a business plan for the creation of a microenterprise that produces ecological bamboo-based toothbrushes in the Quinindé canton of the Esmeraldas province. The investigative context was carried out through bibliographical research, and in conjunction with the descriptive and analytical methods, the data collection was detailed, to obtain information relevant to the object of study, the survey was used and the tools were used as tools, SWOT, SWOT, PESTEL and Porter's 5 forces. The research is based on four methodological phases, in the first phase the environment of the microenterprise was analyzed, in the second phase the potential demand for the product was raised, in the third phase the technical, operational, organizational and legal studies pertaining to the Mypime category. , which is in charge of identifying the inputs and supplies, the design of the plant and the design of the management flow, in addition to the organizational profile that the microenterprise will have, finally in the fourth phase the financial feasibility of the microenterprise was studied. . The investigation concludes that 72.8% of the surveyed population agrees that an ecological toothbrush should be launched on the market to replace plastic brushes, in the financial field it was evidenced that the initial investment corresponds to $21,500.00, recovered in 1 year 11 months and 28 days, with a NPV of $131,152.36, an IRR of 112% and RC/B of $1.31, data that demonstrates the viability of this business plan.